2014
DOI: 10.5194/tc-8-1361-2014
|View full text |Cite
|
Sign up to set email alerts
|

Using MODIS land surface temperatures and the Crocus snow model to understand the warm bias of ERA-Interim reanalyses at the surface in Antarctica

Abstract: Abstract. Moderate-Resolution Imaging spectroradiometer (MODIS) land surface temperatures in Antarctica were processed in order to produce a gridded data set at 25 km resolution, spanning the period 2000-2011 at an hourly time step. The Aqua and Terra orbits and MODIS swath width, combined with frequent clear-sky conditions, lead to very high availability of quality-controlled observations: on average, hourly data are available 14 h per day at the grid points around the South Pole and more than 9 h over a larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 45 publications
(50 reference statements)
5
79
1
1
Order By: Relevance
“…Despite a few deviations from the observations, Crocus captured well the variations of SSA in response to meteorological conditions and metamorphism at Dome C. Since metamorphism strongly depends on the temperature profile close to the surface, this suggests that Crocus successfully resolves the energy budget of the snowpack close to the surface, as already pointed out by Brun et al (2011) andFréville et al (2014). It also proves that the metamorphism parameterization of Flanner and Zender (2006) is appropriate to study snow on the Antarctic Plateau, although this parameterization cannot be strictly assessed in complex conditions as encountered at Dome C. This is promising for larger-scale studies over the Antarctic Plateau and puts Crocus as an appropriate tool to investigate the spatial pattern of SSA over the Antarctic continent (Scambos et al, 2007), which probably results from the combined effects of precipitation, snow drift and metamorphism.…”
Section: Metamorphism Snowfall and Wind-driven Ssa Variationsmentioning
confidence: 49%
See 2 more Smart Citations
“…Despite a few deviations from the observations, Crocus captured well the variations of SSA in response to meteorological conditions and metamorphism at Dome C. Since metamorphism strongly depends on the temperature profile close to the surface, this suggests that Crocus successfully resolves the energy budget of the snowpack close to the surface, as already pointed out by Brun et al (2011) andFréville et al (2014). It also proves that the metamorphism parameterization of Flanner and Zender (2006) is appropriate to study snow on the Antarctic Plateau, although this parameterization cannot be strictly assessed in complex conditions as encountered at Dome C. This is promising for larger-scale studies over the Antarctic Plateau and puts Crocus as an appropriate tool to investigate the spatial pattern of SSA over the Antarctic continent (Scambos et al, 2007), which probably results from the combined effects of precipitation, snow drift and metamorphism.…”
Section: Metamorphism Snowfall and Wind-driven Ssa Variationsmentioning
confidence: 49%
“…ERA-Interim data were already used by Fréville et al (2014) to simulate snow surface temperature on the Antarctic Plateau. As detailed in Libois et al (2014a), precipitation rate was multiplied by 1.5 to ensure that simulated annual snow accumulation matches observations at Dome C. On the contrary, ERA-Interim wind was found in good agreement with measurements performed on the 40 m high instrumented tower at Dome C (Genthon et al, 2013).…”
Section: Reference Simulation (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The surface temperature products of the Greenland Ice Sheet are used as a baseline to investigate future warming trends (e.g. Hall et al 2012), to monitor melt events on the ice sheet (Hall et al, 2013), and as input for surface mass balance or snowpack modeling (Fréville et al, 2014;Shamir and Georgakakos, 2014;Navari et al, 2016). A number of validation studies present results acquired over various time scales and in different locations to 130 determine the accuracy of the MODIS surface temperature products in the cryosphere (Hall et al, 2004(Hall et al, , 2008Koenig and Hall, 2010;Westermann et al, 2012;Hachem et al, 2012;Shuman et al, 2014;Østby et al, 2014;Shamir and Georgakakos, 2014;Hall et al, 2015;Williamson et al, 2017).…”
Section: Remote Sensing Of Surface Temperaturementioning
confidence: 99%
“…ERA-Interim overestimates the sea ice surface temperature compared with the SHEBA observations. A recent study also found that the ERA-Interim simulates a warmer surface temperature over the Antarctic ice sheet due to an overestimation of the surface turbulent fluxes under very stable conditions (Fréville et al, 2014;Jones and Lister, 2014). Because both WRF-Noah and WRF-HIGHTSI apply the same physics schemes for radiation, microphysics, cumulation and the boundary layer, and use the spectral nudging technique to constrain the atmospheric circulation, the differences in simulating the downward radiation and turbulent flux by WRF-Noah and WRF-HIGHTSI are small.…”
Section: Validation Of the Online Simulationmentioning
confidence: 99%